Penerapan Sistem Informasi Persediaan dan Penjualan Pada Toko Sejahtera dengan Menggunakan Program Aplikasi RENE POS 2 - B1031141074, DESY - (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
The purpose of this study is to apply inventory and sales information system in order to assist the process of data processing inventory and sales in Toko Sejahtera to produce efficient and effective information. Author uses qualitative research methods with case study approach. Methods of data collection in the form are observation, interview, and document review. The data analysis unit are RENE Setup, RENE Administration, and RENE Cashier. Methods of data analysis in the form are data reduction and display data in the form of flowchart and then verified. Data validity techniques are triangulation and referential adequacy. Conclusion of this study is the early stage of application of inventory and sales information system by using RENE POS 2 application program at Sejahtera Store which is preparing requirement in hardware and software category.